Professional Values and Motivations: Puerto Rican Journalists in the Digital Age - Lugo-Ortiz, Lourdes (Estudios sobre el Mensaje Periodístico, 2012)
The growing practice of journalism to produce banal, spectacular content has jeopardized the fundamental values of the profession. In this context and through a survey method, this essay explores where Puerto Rican journalists position themselves in regard to the values of the profession and how do they perceive the leadership of the media in which they work. In addition, this work inquires the reasons that motivated them to choose the journalistic profession and the relationship of all these findings with the state of the press today.